The relationship between office environments and employees productivity among non- academic employees at Kolej Al-Quran Terengganu / Nur Syahirah Mohd Ridza - Mohd Ridza, Nur Syahirah (Faculty of Business and Management, 2017)
The physical aspects of a workplace environment can have a direct impact on the productivity, health and safety, comfort, concentration, job satisfaction and morale of the people within it. The quality and quantity of work generated by employees are influenced by the work environment while poor environmental conditions can cause inefficient worker productivity as well as reduce their job satisfaction. The purpose of this research is to study the relationship between office environments and employees productivity among non-academic employees at Kolej AI-Quran Terengganu. The study used Pearson Correlation Coefficient research to identify the relationship between office environments and employee's productivity. The scope of this study was the non-academic employees at Kolej Al-Quran Terengganu. The data of this study were gathered through the distribution of questionnaires using convenience sampling technique. The total of the questionnaires used in this study were 30 questionnaires and give by face to face to the respondents and collected immediately. The data gathered were analyzed by using the Statistical Package for Social Science (SPSS) software version 20. The result of the study has been generated and tabulated and based on the findings, the researcher has successfully achieved the objectives, and the tested hypothesis of this study. Keyword Office environments, productivity.